Marketing Mix Analysis in Enhancing Product Competitiveness in the Local Market : (Case Study on Adam Koi) - Bilqis Nabila Istiqlaliani; Dimas Wahyu Fahriski; Sudarmiatin Sudarmiatin; Ita Prihatining Wilujeng (International Forum of Researchers and Lecturers, 2025)
This study analyzes the application of the 4P marketing mix strategy (product, price, place, promotion) at Adam Koi, a micro-business in the ornamental fish sector. Using a qualitative approach with a descriptive case study method, data was collected through direct observation and interviews with the owner's son, who manages social media and digital marketing. The study reveals that the marketing mix elements are integrated and mutually supportive to maintain competitiveness. In terms of product, Adam Koi focuses on quality by implementing quarantine, care, and high-quality feeding processes to preserve fish color and endurance. For pricing, the strategy is flexible, considering fish type, size, color, and consumer purchasing power. The place aspect utilizes a hybrid distribution system, combining offline and online sales with a focus on safe fish delivery. Promotion has shifted from traditional methods to digital marketing via social media platforms like Instagram to increase audience engagement and expand the market. The findings highlight that the effective use of the marketing mix strengthens competitive positioning, builds customer loyalty, and supports business sustainability. This research also provides practical insights for MSMEs in developing adaptive marketing strategies in the digital era.